Survival of selenium-enriched lactic acid bacteria in a fermented drink under storage and simulated gastro-intestinal digestion. (September 2019) - Martínez, Fernando G.; Cuencas Barrientos, María E.; Mozzi, Fernanda; Pescuma, Micaela
Abstract: Selenium (Se), which is present as SeCys in seleno-proteins, is involved in cancer prevention, thyroid functioning, and pathogen inhibition. Se is incorporated in the diet through Se-containing foods. Some lactic acid bacteria (LAB) can biotransform selenite (toxic) into Se-nanoparticles (SeNPs) and Se-amino acids. To exert their beneficial properties in the host, bacteria should survive the harsh conditions of the gastrointestinal tract and during food storage. We evaluated whether selenization of LAB influenced bacterial growth and survival during gastrointestinal digestion and after storage when present in a fermented fruit juice-milk (FJM) beverage. Lactobacillus brevis CRL 2051 and Fructobacillus tropaeoli CRL 2034 were grown in MRS with and without selenite, and used to inoculate the FJM matrix. Selenization had no effect on LAB growth (9.54–9.9 log CFU/mL) in the FJM drink. The presence of SeNPs was confirmed for both selenized strains in the FJM beverage; however, the highest Se concentration (100 μg/L) was detected for the fermented beverage with selenized L. brevis . Under storage conditions 1.1 log CFU/ml decrease in cell count of selenized cells of L. brevis was observed, while no effect on cell viability was detected for non-selenized L. brevis or both selenized and control cells of F. tropaeoli . Resistance of L. brevis during digestion of the fermented FJM beverage was not affected by selenization. Contrarily, an increase (1 log CFU/mL) in the resistance of F. tropaeoli was observed when cells were selenized. After digestion, Se was detected in the soluble fraction of the beverage fermented by both strains, being higher for L. brevis (23.6 μg/L). Although selenization did not exert a drastic effect on strains´ survival during storage and digestion, microbial selenization previous to food fermentation could be an interesting tool for Se enrichment avoiding thus the addition of toxic Se salts. Graphical abstract: Unlabelled Image Highlights: Fruit/milk juices were successfully fermented by selenized lactic acid bacteria. Se-enrichment slightly affected bacterial survival under storage and digestion. Selenized cells are an interesting tool for Se food enrichment. Selenization of Fructobacillus tropaeoli is for the first time reported.